[Eastern Telecom case ; Sexual abuse at home ; Singing telegrams [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
A report on charges of crony capitalism and unfair treatment of shareholders in Eastern Telecoms. Looks at the children who are sexually abused at home. A piece of birthday greetings brought to your home via singing telegram.